Constitutional Aspect of the United Kingdom and Sri Lanka Foreign Policy Decision Making (1977-2016) - Kandaudahewa, Hasith Eranda (Indus Foundation of Research, Education and Social Welfare, 2016)
This paper mainly focuses on Constitutional Aspects of UK-Sri Lanka Foreign Policy Decision Making process between UK-Sri Lanka between 1977 to 2016.Major significant of selected period based on acceptance of 3rd party involvement as well as hegemonic power influence to bilateral relations. UK-Sri Lanka relations started from 1815 as a Colonial ruler and continued even after independence in 1948. During the post-Cold war era UK-Sri Lanka maintain close relationship within the international paradigm due to national interest.UK-Sri Lanka Political and Economic relations reach ripe movement during the ethnic conflict and United Kingdom (UK) became a major party for conflict prevention and negotiation process. However, escalation of ethnic conflict create more British involvement in Sri Lankan decision making process and Sri Lanka was granted large scale political and financial aid to maintain the peace process. During the last stage of humanitarian mission against the LTTE, UK became a more active party and their influence into Sri Lankan politic effected on both horizontal and vertical level decision making.
Keywords: Executive Power, Sri Lanka and UK Foreign Policy, Lobbing Groups, Post-war era.